Pemberdayaan Guru SD melalui Pelatihan Pembuatan Tempat Sampah Otomatis Berbasis Arduino - Sujono Sujono; Mochammad Syafiuddin Shobirin; Wilujeng Amelia; Arfia Rahmi Febrianti; Dimas Wahyu Listyawan; Mochammad Risqi Albani (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to empower elementary school teachers by enhancing their knowledge and skills in utilizing simple microcontroller-based technology. The training was conducted at SD Negeri Bakalan, Sumobito District, Jombang Regency, targeting elementary school teachers. The materials included an introduction to Arduino and hands-on practice in building an automatic trash bin using sensors. The methods applied were lectures, demonstrations, and guided practice. The results show that participants were able to understand the basic concepts of Arduino and successfully assemble the automatic trash bin with assistance. Furthermore, the activity improved teachers’ technological literacy and raised awareness of the importance of simple innovations to support thematic learning, particularly in science and environmental education. This program successfully provided empowerment for elementary school teachers as change agents who can integrate technology and environmental awareness into the learning process.